Efficacy of Probiotics in the Treatment of Adult Female Bacterial Vaginosis: A Meta-Analysis - Yuping Shan; Zicheng Cui; Zhaoxia Ding; Yushuang Yao; Aiping Chen (IMR Press, 2023)
Background: The purpose of this meta-analysis was to assess the value of probiotics in the treatment of adult female bacterial vaginosis (BV). Methods: We looked for published randomized controlled trials in PubMed, Embase and The Cochrane Library from the inception dates of the database to January 3rd, 2022. We conducted the search focusing on the treatment of adult female BV with probiotics. Two independent researchers screened the literature, evaluated the trial quality and extracted the data according to the inclusion and exclusion criteria. The primary outcome was the ratio of patients with BV with recurrence according to Nugent score 7-10 for recurrence after treatment. After heterogeneity was assessed using Review Manager 5.4 software, meta-analysis and bias assessment were performed using Stata 17.0 software. Results: A total of 5 articles representing 425 patients were included in this meta-analysis. Compared with antibiotics alone or antibiotics combined with a placebo, probiotics or probiotics combined with antibiotics significantly reduced the rate of recurrence at around the 30th day (risk ratio (RR) 0.11; 95 % confidence interval (CI) 0.03-0.33). However, in the analysis of heterogeneity, we found that after 30 days, the therapeutic effect of probiotics decreased with the extension of follow-up time (RR 0.50; 95% CI 0.24-1.03), (RR 1.24; 95% CI 0.88-1.76). Conclusions: The short-term efficacy of probiotics in the treatment of BV in adult female patients may be satisfactory, but the long-term efficacy of probiotic therapy may be suboptimal and still requires validation by further clinical trials.